PENGARUH ARUS KAS BEBAS, KEBIJAKAN DIVIDEN DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2012 - WISNU SOFIA RAKHMAN, ANDHIKA (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: The purpose of this study was to analyze the influence of free cash flow. dividend policy and firm size on capital structure . Free Cash Flow is proxied by free cash flow (FCF) , dividend policy is proxied by the dividend payout ratio (DPR), firm size is proxied by the natural logarithm of total assets, while capital structure is proxied by LTDtER (Long Term Debt to Equity Ratio). Sampling was done by using purposive sampling method that produces 22 companies as the study sample. Multiple linear regression was used to examine the relationship between the dependent and independent variables. The results showed that the independent variables simultaneously affect the capital structure. Partially free cash flow positive effect on the capital structure of the firm size also has a positive effect on the capital structure, while the dividend policy has negative effect on the capital structure. Keywords: capital structure, free cash flow, dividend policy and the firm size.